المنهاج المدرسي وعلاقته بتعزيز التربية الصحية لذى التلاميذ. - مكي, بلقاسم (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2019)
يعتبر المنهاج المدرسي انعكاس لفلسفة خصوصية المجتمع، لذا وجب علينا كدارسين في ميدان علم اجتماع التربية أنْ نبحث و نحلل مضامين هذه البرامج بما تشتمل عليه من مواد تربوية تعليمية حول قضايا التربية الصحية لكونها تساهم في تعزيز و توعية التلاميذ على الممارسات الصحية السليمة ، و بالتالي العمل على تنشئتهم وفق قواعد و مبادئ صحية متعارف عليها لأن الغاية السامية من وجودنا هي المحافظة على أغلى ما نمتلكه من صحة و عافية لأنه لا حياة بدون أن نَنْعم بالصحة و العافية ،و هذا ما توصلنا إليه في دراستنا هذه حيث تبيَن أن المنهاج المدرسي له علاقة قوية بما تتضمنه من اهتمام بقضايا التربية الصحية سواءً تعَلق الأمر بالنظافة و كذا بتثْقيف التلاميذ بالنظام الغذائي الصحي المفيد ولا ننسى اهتمامه بممارسة النشاطات الرياضية ، كل هذا من أجل صحة أفضل لأن الصحة هي الحياة. Study Summary The school curriculum is a reflection of the philosophy of the privacy of the community. Therefore as educators in the field of sociology of education, we have to examine and analyze the contents of these programs, including the educational materials on health education issues, as they contribute to the promotion and awareness of students on healthy health practices, To raise them in accordance with the rules and principles of health recognized because the goal of our existence is to maintain the most expensive of what we have health and wellness because it is not life without health and wellness, and this is what we found in our study, where it was found that the curriculum has a strong relationship Including the eh Be aware of the issues of health education, whether it is clean, as well as to educate students healthy diet useful and do not forget his interest in sports activities, all for better health because health is life